The Effect of Traditional Transportation Using Cool Box on Quality of Fresh Milk and Frozen Milk from Peternakan Sapi Terpadu Sangatta to Samarinda East Kalimantan - Arif Ismanto; Fikri Ardhani; Marhamah Marhamah (Buletin Peternakan, 2018)
This study was aimed to determine the quality of milk before and after through the transportation process as far as ± 180 km for ± 4 hours from Peternakan Sapi Terpadu, North Sangata to Samarinda. This research used 2 treatments: frozen and fresh milk. Preliminary tests carried out before the transport process, while the final tests carried out after transportation including parameters of chemical composition, physical quality and organoleptic quality. Data were analyzed by statistic t-test. The results showed that the physical, chemical and organoleptic attributes (except viscosity) of frozen and fresh milk were not significantly different before and after transportation. The viscosity of frozen milk before and after transportation were 1.0212 and 1.0277 g/cm3 respectively, while on fresh milk were 1.0265 and 1.0272 g/cm3, respectively. The freezing point of milk before and after transportation was -0.445 to -0.527ºC for frozen milk and -0.480 ºC to 0.490ºC for fresh milk. Protein content before and after transportation was 2.52% to2.78% for frozen milk and from 2.78 % to 2.87% for fresh milk. The fat content before and after transportation was 6.78% to 5.04% for frozen milk and from 3.73% to 4.04% for fresh milk. The lactose content before and after transportation that is from 13.66% become 13.21% for frozen milk and 11.33% to 11.88% for fresh milk. The total solid content before and after transportation was 13.66 % and 13.21% for frozen milk and 11.33% to 11.88% for fresh milk. The SNF content before and after transportation was 6.88 % to 8.17 % for frozen milk and from 7.60% to 7.84% for fresh milk. It can be concluded that traditional transportation of milk from Peternakan Sapi Terpadu to Samarinda did not affect the organoleptic, physical, and chemical except viscosity of milk.